Need For Orthopedic Dental Care of Adult Urban Population of The Republic of Kazakhstan - Ruzuddinov N.S; Gaffarov S.А; Ruzuddinov S.R (Genius Journals, 2021)
Mass dental examinations of the adult population of the Republic of Kazakhstan were conducted. 3 age groups were examined: People living in the city of Almaty were selected for the study: middle (45-59 years old), elderly (60-79 years old) and senile (80 years and older). The studied individuals were found to have a high loss of teeth, which is 79.3% of the urban and urban population. The most common dental defects are found in the elderly age group 59.4%, and in older people 30.9%. A high frequency of complete absence of teeth was revealed in the elderly 24.2%, and in the senile 48.0%. The results of the dental examination require improvement of orthopedic dental care in the Republic of Kazakhstan
Keywords: Needs; treatment; dental care; orthopedic treatment